A randomized controlled trial of mindfulness: effects on academic stress, academic burnout, and psychological resilience in university students - Chen, Shanwei; Qi, Xiuzhi (Frontiers in Psychology, 2025)
IntroductionAcademic stress, academic burnout, and reduced psychological resilience are prevalent among university students, particularly during examination periods. This study evaluated the effectiveness of an 8-week structured mindfulness training program in improving these outcomes.MethodsA randomized controlled trial (RCT) was conducted with 153 undergraduate and graduate students who were randomly assigned to a mindfulness intervention group (n = 77) or a minimal-contact control group (n = 76). Intention-to-treat (ITT) analysis was performed using linear mixed models with likelihood-based estimation under the missing-at-random assumption.ResultsAt the primary endpoint (Week 8), the intervention group showed significantly lower academic stress compared with the control group (B = 14.79, 95% CI [12.96, 16.62], p < 0.001, Cohen's d = −1.89). Secondary outcomes demonstrated parallel benefits, including reduced academic burnout (B = 11.31, 95% CI [8.62, 14.00], p < 0.001, d = −1.26) and increased psychological resilience (B = −18.42, 95% CI [−20.94, −15.90], p < 0.001, d = 2.02). These effects were largely sustained at the 2-week follow-up.DiscussionThe findings indicate that structured mindfulness training significantly decreases academic stress and burnout while enhancing psychological resilience among Chinese university students. These results support the value of integrating mindfulness-based programs into higher education mental health initiatives.